Translating English for Specific Purposes (ESP) : A Strategy Analysis - Mahriza, Rita; Meisuri, Meisuri; Tangkas, I Wayan Dirgayasa; Setiasari, Winda; Damaiyanti, Susi (JADEs Journal of Academia in English Education, 2023)
This study is about translation strategies for translating English for Specific Purposes (ESP). The strategies applied refer to Vinay and Dalbenet Theory, which consists of Direct (Borrowing, Calque, Literal, and Transposition) and Oblique methods (Modulation, Equivalent, and Adaptation). This study aims to determine the strategies students apply when translating ESP texts and how the students' educational backgrounds impact this process. Descriptive qualitative was applied as the methodology using tests and interviews to collect the data. The result showed that 6 of 7 translation strategies are implemented by translators. To implement direct translation, it has applied all strategies: borrowing, calque, literal translation, and transposition strategies. Thus, oblique strategies are used in equivalent and adaptation strategies, but modulation strategies did not exist from the target language. The next issue is that the background significantly influences the accuracy of word choice in the target language. Some translators acknowledge needing help translating vocabulary that seems more common than some terminology they frequently encounter when taking the classes.